Artistic Expression: Another Challenge for Rural Education - Sonia Álvarez-Castro; María del Carmen Domínguez-Lacayo (Revista Electrónica Educare)
This paper identifies the parameters required to create opportunities that would strengthen the social fabric and would promote a comprehensive development through the artistic expression as a method for expressing feelings and constructing –cultural and social– identities as individuals, which, in our global context have been eroded by the homogenization of experiences.